Aplicação de fasores dinâmicos na localização de defeitos em linhas de transmissão aéreas - Costa, Thassiana Batista da (2019)
This thesis proposes a method based on dynamic phasor for the detection and location of fault in overhead lines and underground cables. Instead of using the traditional formulation of the dynamic phasor based on amplitude modulation, this thesis proposes to use a formulation based on frequency modulation, as it was found that the frequency modulation increases the transient signals associated with the fault, thus improving its detectability. The frequency modulation was synthesized based on the signals obtained by a PLL (Phase-Locked Loop) circuit. Thus, in order to investigate the adequacy of the PLL for this task, an initial test considering the PLL as a PMU (Phasor Measurement Unit) was performed. Then, the PLL was also implemented in a DSP (Digital Signal Processor). Several test cases including harmonic polluted environments were used to evaluate the performance of the PLL as a PMU. The algorithm based on the frequency modulation was then tested for the high impedance fault location, as they tend to present low observability and remain a challenge for several actual networks. The results indicate the adequacy of the proposed scheme as the algorithm was able to maintain a suitable level of accuracy, regardless of the fault considered.Também disponível on-line.